2012
DOI: 10.1002/eji.201141907
|View full text |Cite
|
Sign up to set email alerts
|

Transcript profiling of CD16‐positive monocytes reveals a unique molecular fingerprint

Abstract: CD16-positive (CD14 ++CD16

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(74 citation statements)
references
References 30 publications
3
71
0
Order By: Relevance
“…In a previous study, Frankenberger et al (44) reported that M16 expressed a lower level of CD14 and CD163 transcripts with respect to M14. In the present study, we corroborate that the expression of key phenotypic markers of MMfs (CD14, CD163, CD209, and FRb) (29) is greatly diminished in M16, whereas they abundantly express the GM-CSF-associated marker CLEC5A (34).…”
Section: Discussionmentioning
confidence: 91%
“…In a previous study, Frankenberger et al (44) reported that M16 expressed a lower level of CD14 and CD163 transcripts with respect to M14. In the present study, we corroborate that the expression of key phenotypic markers of MMfs (CD14, CD163, CD209, and FRb) (29) is greatly diminished in M16, whereas they abundantly express the GM-CSF-associated marker CLEC5A (34).…”
Section: Discussionmentioning
confidence: 91%
“…[SAGE]) technologies. 11,12,28,29 For the present study, we have used the highly sensitive MACE approach for determination of the transcriptome. 22 When comparing the present results to the previous SuperSAGE approach, 11 we found a similar gene expression pattern for monocyte subsets.…”
Section: Discussionmentioning
confidence: 99%
“…15 It has clearly been shown previously that the CD16-positive monocytes cocluster with monocytes and not with DCs. 29,32,33 Still, one could hypothesize that the slan-positive subset of the CD16-positive monocytes might have a gene expression pattern matching that of DCs. Evidence supporting the concept that slan-positive cells and DCs are distinct has been published earlier, in that TLR3, -4 and -10 transcripts did show a reciprocal expression pattern in slan-positive cells and DCs.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the CD16 + subset accounts for only 10% of the total monocyte population in healthy donors, displaying a unique cell-surface marker expression and cytokine secretion pattern in comparison with its CD16 − counterpart [13,14]. Indeed, upon stimulation with lipopolysaccharide, CD16 + monocytes isolated from healthy donors secrete higher amounts of pro-inflammatory factors such as tumor necrosis factor-alpha (TNFα), interleukin-1-beta (IL-1) and IL-6, but low amount of the anti-inflammatory mediator IL-10 [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%